Nalar keilmuan buku referensi filsafat pendidikan Islam di Indonesia - Sabarudin, Sabarudin; Arif, Mahmud (Ta'dibuna: Jurnal Pendidikan Islam, 2022)
The reference books on philosophy of Islamic education can be analyzed from two perspectives: as a culture product and as a culture producer. By the first perspective, the reference books are reflection of "dominant episteme”, whereas by the second one, the reference books had constructed a domain of public knowledge. Based on this, the reference books have epistemic and authoritive functions for an academic actualization process. In such case, the reference books were assumed as the ideal texts. The reference books that have been studied that have been written by the Indonesian scholars, generally have still being characterized by normative-reproductive reasoning. The normative nuances were depicted by textual, analogical, and declarative reasoning, while the reproductive ones were showed by their poor relevance and justificative in model. In addition to these, they weren't able to stimulate intellectual discourses, because of their trivial tendencies. Consequently, the concept of Islamic education tends to be "static motion”, because there is no a firm endorsement from empirical researches, critical paradigms, and progressive formulation. Buku-buku referensi filsafat pendidikan Islam bisa dianalisis dari dua perspektif, yaitu sebagai produk budaya dan produsen budaya. Dari perspektif pertama, buku referensi adalah cerminan nalar dominan, sedangkan dari perspektif kedua, buku referensi membangun ranah pengetahuan publik. Dengan demikian, buku referensi memiliki fungsi epistemik dan otoritatif bagi proses aktulaisasi akademik. Di sini buku referensi dianggap sebagai ”teks ideal”. Buku referensi yang dikaji ini ditulis oleh sarjana Tanah Air, yang secara umum masih ditandai dengan penalaran normatif-reproduktif. Nuansa normatif tergambar oleh penalaran tekstual, analogis, dan deklaratif, sedangkan nuansa reproduktif ditunjukkan oleh relevansi yang minim dan model justifikatif. Selain itu, buku referensi tersebut kurang mampu merangsang wacana intelektual karena kecenderungan trivialnya. Konsekuensinya, konsep pendidikan Islam mengarah pada gerak di tempat karena lemahnya dukungan riset empiris, paradigma kritis, dan formulasi progresif.